Total time of operation is a risk factor of stroke-associated pneumonia in acute ischemic stroke patients with intra-arterial treatment. Issue 29 (July 2016) - Liu, Rui; Li, Wei; Li, Yaoyang; Han, Yunfei; Ma, Minmin; Zhu, Wusheng; Li, Min; Dai, Qiliang; Cao, Yuezhou; Xu, Gelin; Liu, Xinfeng
Abstract: Background and purpose: Stroke-associated pneumonia (SAP) is associated with poor functional outcome in patients with acute ischemic stroke (AIS). The objective of this study was to identify predictors of SAP in patients underwent intra-arterial treatment (IAT). Methods: Consecutive patients with AIS within 6 h from the symptom onset underwent IAT were enrolled. Independent predictors of in-hospital SAP after AIS were obtained using multivariable logistic regression. Kaplan–Meier survival curves were calculated and compared by the log-rank test. Results: Of 165 patients with AIS in the study period, 102 (61.8%) underwent IAT. Twenty-two (21.6%; 95% confidence interval [CI], 14.7–29.4) experienced SAP. Patients with SAP were older (69.2 vs 62.9 years, respectively; P  = 0.011), more severely affected (National Institutes of Health Stroke Scale score, 18 vs 9, respectively; P  = 0.004), more likely to underwent symptom of dysphagia (86.4% vs 15%, respectively; P  < 0.001), lower Glasgow Coma Scale score (9 vs 13, respectively; P  < 0.001), and longer operation time (149.5 vs 123, respectively; P  < 0.001) than those without SAP. Only symptom of dysphagia (adjust odds ratio [OR], 12.051; 95% CI, 3.457–50.610; P  < 0.001) and total time of operation (adjust OR, 1.040; 95% CI, 1.009–1.071; P  < 0.001) were identified as independent predictors of SAP. Patients with SAP had stable or improved deficits after AIS with IAT ( P  < 0.001). Conclusions: Besides dysphagia, total time of operation is a risk factor of SAP in patients with AIS with IAT.